УПРАВЛЕНИЕ ВОЗБУЖДЕНИЕМ СИНХРОННЫХ МАШИН С ИСПОЛЬЗОВАНИЕМ ФУНКЦИИ КОМПЛЕКСНОЙ ОШИБКИ - Агамалов, О.Н. (Інститут електродинаміки НАН України, Київ, 2012)
In the report the new concept of the automatic voltage regulator (AVR) and power system stabilizer (PSS) of the synchronous machines is considered. It is known, that the primary goal, that solved AVR are maintenance of a terminal voltage of the synchronous machine according to the reference. For PSS the goal is mitigation the electromechanical oscillations of the synchronous machine at various disturbances. For these purposes as inputs of AVR and PSS the set of state variables of the synchronous machine is used: terminal voltage, armature current, frequency, speed, power, etc. The key feature of offered automatic excitation regulator (AER) is use only the phasor terminal voltage for the decision of all above-stated problems, that considerably reduces influence of noises and disturbances, simplifies its design and operation. References 8, figure 1.